Analysis of the Effect of Infrastructure Development on Economic Growth in Mataram City - Solihatun Mardiah; M. Irwan (Tinta Emas Institute, 2024)
Economic growth is an indicator to see useful development results and to determine the direction of future development. A positive economy is an economy with increasing growth, while a negative economy is a decline in growth. This study aims to analyze how much influence infrastructure development has on economic growth in Mataram City. The data used is secondary data from 2009 to 2023 sourced from PLN, Public Works and Spatial Planning Office, and PDAM Giri Menang. The research approach uses a quantitative approach. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that the Highway variable had a significant effect on economic growth, the Electricity variable was significant to economic growth, and the water variable had a significant effect on economic growth.